Study Of The Influence Of Public Expenditure And Macroeconomic Variables On The Happiness Index In Sumatera - Merri Anitasari; Yesi Indian Ariska (UNIVED Press, 2025)
This study aims to analyze the effect of public spending and macroeconomic variables (local government size, per capita GRDP, Gini coefficient, unemployment, inflation and tax revenue) on the happiness index in Sumatra. The types of data used in this study are cross-section data and time series data. Cross-section data covers 10 provinces in Sumatra, namely Aceh, North Sumatra, West Sumatra, Riau, Jambi, South Sumatra, Bengkulu, Lampung, Bangka Belitung Islands and Riau Islands. While the time series data consists of data from 2014, 2017 and 2021. The data sources are secondary data from the Central Statistics Agency and the Directorate General of Fiscal Balance, Ministry of Finance. The data were analyzed using the panel data regression method with the Common Effect Model approach. The results of the study show that Per Capita Income and Inflation have a significant effect on the happiness index in Sumatra. Meanwhile, public spending, local government size, Gini coefficient, unemployment rate, and local tax revenue do not show a significant effect on happiness. These findings suggest that while economic factors and the size of local government play an important role in improving well-being, the direct impact on people's happiness is influenced by a complex of other factors, including people's perceptions, social inequality, and the efficiency of resource management.